Effectiveness of Online Based Nutrition Education in Increasing Knowledge and Self-Efficacy - Rachmah, Qonita; Haryana, Nila Reswari; Rifqi, Mahmud Aditya; Diana, Rian; Atmaka, Dominikus Raditya; Setyaningtyas, Stefania Widya; Nastiti, Aliffah Nurria; Agustin, Asri Meidyah (Universitas Airlangga, 2024)
The latest COVID-19 pandemic has taught the importance of nutrition and immunity to prevent diseases, in which case the fatality rate exceeded 2.58%. Immunity is believed to be one of the critical efforts to prevent the spread of COVID-19. This is, for sure, inseparable from nutritional intake, exercise, and environmental factors. However, that needed to be better understood by many people. This study aims to assess the effectiveness of online-based nutrition education in increasing knowledge and self-efficacy to maintain a balanced nutritional intake and implement hygiene. Online-based nutrition education was done using video conference by Zoom conference and text-based education methods using Telegram. Each session is held for approximately two hours. Samples were all collected voluntarily, comprising an adult population aged 19 – 5 . Knowledge and self-efficacy were measured using a structured questionnaire. In total, 217 samples were recruited. 92.2% of participants were female, the average age was 29 ± 10.04, 34.1% worked as civil servants, and the majority, 52.1%, came from East Java. Education with the digital learning method succeeded in increasing nutritional knowledge from a score of 55.9 to 91.8 (p<0.000) and significantly increasing self-efficacy of consuming balanced-nutritious food and self-efficacy of a clean and healthy lifestyle (p<0.000). In conclusion, online-based nutrition education proved effective in increasing knowledge and self-efficacy. Hence, program duplication with a broader range of subjects can be done nationally.